EKSPLORASI PEMBELAJARAN MAHARAH KALAM MELALUI METODE MUHADATSAH DI PONDOK PESANTREN DARUNNAJAH - Muhajir, Nirmalasari; Muyassaroh, Nurul; Niharsono, Azahra; Karimah, Khikmatul; Muasomah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explain how the Muhadatsah (conversational practice) method is utilized to teach speaking skills (maharah kalam) at the Darunnajah Islamic Boarding School in Jakarta, to determine the method's role in enhancing students' speaking abilities, and to describe the use of a bi'ah lughawiyah (language environment) that supports Arabic language learning. The research employed a qualitative descriptive approach combined with a case study method. Data collected through observation, interviews, and documentation were analyzed using the Miles and Huberman interactive analysis model, which encompasses data reduction, data display, and conclusion drawing and verification. The findings indicate that the Muhadatsah method is implemented through conversations, discussions, presentations, role-playing, and the habit of using Arabic in daily life. This method proved effective in improving students' speaking skills, evidenced by gains in vocabulary, fluency, sentence construction, listening comprehension, and communicative confidence. The bi'ah lughawiyah manifested through the use of Arabic in classrooms, dormitories, organizations, public speaking sessions (muhadarah), language laboratories, and various other boarding school activities facilitates better learning outcomes. Consequently, the Muhadatsah method, when combined with a conducive language environment, serves as an effective approach for enhancing students' communication skills, particularly in speaking. This method can also serve as a model for developing Arabic language instruction in Islamic educational institutions.